Content Validation of the User Attitudinal Component and Factors in Green Building (International Journal of Built Environment and Sustainability, 2019)
The green building performance gap has been well acknowledged in building industry and one of the contributors to these issues is the behaviour of users in the building. One of the element that influences the behaviour of users is the attitude of the user towards the building environment. The consideration of the human aspects especially the user attitudinal component and factor is essential as an approach in improving the building performance. This paper aims to identify the user attitudinal component and factor from the literature and to validate the research instrument by using the content validation method. The procedure of content validity include the conceptualization and development of instrument throughout an extensive literature review and to validate the relevance of the user attitudinal component and factors to be considered in green buildings. Three user attitudinal components and seventeen factors were developed from the extensive review of the literature. Ten experts were chosen to appraise the instrument of research by using a quantitative content validation. Fifteen items were accepted as relevant to the study within the accepted range and two items were eliminated from the research instrument. The study’s output allows the building industry a new insight on what user attitudinal aspect to be considered and integrated when dealing in the development of green building. The output of this study greatly benefits the building designers and managers when designing, constructing and managing green buildings.
Keywords: Green Building; User Attitude Component and Factor; Content Validation